Mind Mapping-Enhanced Reading Comprehension to Indonesia Islamic Junior High School Students: An Action Research - Dewi Nopita; Satria Agust; Yuni Indriani (J-SHMIC : Journal of English for Academic, 2021)
This classroom action research was conducted in a State Islamic Junior High School in Tanjung Pinang at the 8th grade in academic year 2020-2021. The purpose of the research was to describe how mind mapping can improve students’ reading comprehension of descriptive texts. The participants of the research consisted of 27 students. To gather the research data, the researchers used observation and test. The test was administered three times (pre-test, post-test 1, and post-test 2). Then, the data got from the observation were analyzed qualitatively while those from test were analyzed quantitatively. The result of pre-test was 9 students (33,3%) scored ≥70. In the post-test first cycle, the score of 16 students (59,25%) was ≥70, and in the post-test cycle II, 20 students (74,1%) scored ≥70. The results of the tests showed that the number of students who got score ≥70 improved. Meanwhile, the result of the observation showed that the use of mind mapping was successful in improving students’ reading comprehension. The students became more interested and more motivated to learn. It showed that ≥70% of the students participated actively in the teaching and learning process. Therefore, it is recommended for teachers to use this technique to upgrade students’ learning achievement.